'They Came to Sneer, and Remained to Cheer': Interpreting the 1934–35 England Women's Cricket Tour to Australia and New Zealand. Issue 17 (21st November 2016) - Ryan, Greg
Abstract: This paper focuses generally on the history of women's cricket during the earlier twentieth century, primarily on the 1934–35 England women's cricket tour of Australia and New Zealand, and more so on the New Zealand dimension. The tour occurred at a critical time for women's team sport in both countries in that from the 1920s consistent local and then national competitions brought continuity to previously fragmented activities. Hence the tour provides a useful barometer for a wide range of attitudes to sporting participation by women and reveals contrasts between Britain and Australasia. At the same time, there are specific attitudes to the playing of cricket by women that need to be explored. Here there are some obvious differences between accounts in dedicated women's cricket sources and the specialist women's press, both of which sought to encourage the game on its own terms, and those in sources with a broader scope and male-dominated editorship which were more inclined to trivialize and disparage women's cricket and to judge it against the men's game.